Pengaruh Independensi, Pengalaman Kerja, Due Profesional Care, Akuntanbilitas dan Besaran fee Audit Terhadap Kualitas Audit - nanda islami, ozalea putri (2016)
This research aimed to analyze the influence of independence, work experience, due professional care, accountability and audit fee on audit quality owned Public Accounting Firm in Jawa Tengah and DIY. This research was a quantitative one using primer data from questionnaire. The population of this research are all auditors working on the Public Accounting Firm in Jawa Tengah and DIY. The sample of this research are 52 respondents. Determination of samples by using covinience sampling method. The analysis method of this research using multiple regression analysis, F-test, coeffitient determination R2, and t-test. This research proved that independency, work experience, due professional care, accountability and audit fee influenced audit quality.